‘Ali Shari’ati and the Shaping of Political Islam in Iran - Chatterjee, K. author. aut Link
XIV, 274 p.
Keywords: This book tells the story of how Shari'ati developed a language of political Islam, speaking in an idiom intelligible to the Iranian public and subverting the Shah's regime and its claim to legitimacy.